2011
DOI: 10.1002/uog.8966
|View full text |Cite
|
Sign up to set email alerts
|

Increased uterine artery pulsatility index at 34 weeks and outcome of pregnancy

Abstract: Objectives To evaluate pregnancy outcome in patients with increased uterine artery (UtA) pulsatility at 34 weeks' gestation as an isolated finding. Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
3
22
0
Order By: Relevance
“…Maroni et al evaluated pregnancy outcome in patients with increased uterine artery PI at 34 weeks' gestation and reported higher chance of delivering SGA babies, but the risk of other complications was not increased [32]. They suggested reassessment of uterine artery Doppler at 26 to 28 weeks in those with increased resistance in the second trimester of pregnancy as we also concluded.…”
Section: Discussionsupporting
confidence: 55%
“…Maroni et al evaluated pregnancy outcome in patients with increased uterine artery PI at 34 weeks' gestation and reported higher chance of delivering SGA babies, but the risk of other complications was not increased [32]. They suggested reassessment of uterine artery Doppler at 26 to 28 weeks in those with increased resistance in the second trimester of pregnancy as we also concluded.…”
Section: Discussionsupporting
confidence: 55%
“…However, the UtA pulsatility has been shown to be persistently increased until the late-trimester in approximately 30% of the low-risk population, although its association with obstetric complications is unclear [8,10].…”
Section: Introductionmentioning
confidence: 98%
“…Essentially, Doppler studies were carried out in pregnancies presenting with PE or fetal growth restriction reported that the outcome was worse if there was increased, rather than normal, impedance to flow in the uterine arteries [16,17,18,19,20,21,22]. Similarly, studies investigating pregnancies with abnormal uterine artery Doppler at 20-24 weeks' gestation reported that outcome was worse in those with persistence of high impedance to flow during the third trimester compared to those with normalization in flow [23,24,25]. …”
Section: Introductionmentioning
confidence: 99%